2017
DOI: 10.1016/j.econlet.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Does the truth come naturally? Time pressure increases honesty in one-shot deception games

Abstract: Many situations require people to act quickly and are characterized by asymmetric information.Since asymmetric information makes people tempted to misreport their private information for their own benefit, it is of primary importance to understand whether time pressure affects honest behavior. A theory of social heuristics (the Social Heuristics Hypothesis, SHH), predicts that, in case of one-shot interactions, such an effect exists and it is positive. The SHH proposes that when people have no time to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 51 publications
4
90
1
5
Order By: Relevance
“…The case of honesty is particularly interesting. When players do not initially know the payoffmaximizing strategy, then System 1 promotes honesty (Foerster et al, 2013;Capraro, 2017;Capraro et al, 2019), and this is in line with the predictions of the GSHH. However, when players know the available actions and their consequences since before the cognitive process manipulation, then System 2 promotes honesty, especially when dishonesty harms an abstract other (Köbis et al, in press).…”
Section: Limitations Of the Gshh And Directions For Future Researchsupporting
confidence: 70%
“…The case of honesty is particularly interesting. When players do not initially know the payoffmaximizing strategy, then System 1 promotes honesty (Foerster et al, 2013;Capraro, 2017;Capraro et al, 2019), and this is in line with the predictions of the GSHH. However, when players know the available actions and their consequences since before the cognitive process manipulation, then System 2 promotes honesty, especially when dishonesty harms an abstract other (Köbis et al, in press).…”
Section: Limitations Of the Gshh And Directions For Future Researchsupporting
confidence: 70%
“…Two early studies using time constraints to manipulate cognitive mode found that honesty requires deliberation (Gunia et al, 2012;Shalvi et al, 2012). This conclusion was challenged by three more recent studies, two of which found the opposite effect, that time pressure promotes honesty (Capraro, 2017;Lohse et al, 2018), while the third one found a null effect (Barcelo & Capraro, 2017). Studies using different cognitive processing manipulations, such as conceptual priming of intuition (Cappelen et al, 2013), ego-depletion (Gino, Schweitzer, Mead & Ariely, 2011), and cognitive load (van't Veer, Stel & van Beest, 2014) have also led to mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have also conducted a time pressure study (analyzed in the Appendix). This is a significant contribution in itself, because the role of time pressure and, more generally, the role of intuition on honesty has been at the center of the debate in the last years (Andersen et al, 2018;Cappelen et al, 2013;Capraro, 2017;Capraro et al, 2019;Debey et al, 2012;Gino et al, 2011;Gunia et al, 2012;Lohse et al, 2018;Mead et al, 2009;Shalvi et al, 2012;Spence et al, 2001;Van't Veer et al, 2014;Walczyk et al, 2003), as a part of the more general research program of classifying social behaviors according to whether they are intuitive or reflective Cococcioni, 2015, 2016;Capraro et al, 2017;Corgnet et al, 2015;Lotz, 2015;Rand et al, 2012Rand et al, , 2014Rand et al, , 2016Rand, 2016). In our case, time pressure has no effect on the overall rate of honesty.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, economists and psychologists have started studying (dis)honesty using incentivized economic problems (Erat and Gneezy, 2012;Fischbacher and Föllmi-Heusi, 2013;Gneezy, 2005;Hurkens and Kartik, 2009;Kartik, 2009;Schweitzer, 2014, 2015;Mazar et al, 2008;Sheremeta and Shields, 2013;Weisel and Shalvi, 2015;Wiltermuth, 2011). For example, they have explored the effect on honesty of many exogenous and endogenous variables, such as: demographic characteristics (Abeler et al, 2019;Biziou-van Pol et al, 2015;Cappelen et al, 2013;Capraro, 2018;Childs, 2012;Dreber and Johannesson, 2008;Friesen and Gangadharan, 2012;Erat and Gneezy, 2012); social and moral preferences (Biziou-van Pol et al, 2015;Schweitzer, 2014, 2015;Shalvi and De Dreu, 2014); incentives (Dreber and Johannesson, 2008;Erat and Gneezy, 2012;Ezquerra et al, 2018;Fischbacher and Föllmi-Heusi, 2013;Gneezy, 2005;Gneezy et al, 2018;Kajackaite and Gneezy, 2017;Mazar et al, 2008); and cognitive mode (Andersen et al, 2018;Cappelen et al, 2013;Capraro, 2017;Capraro et al, 2019;Gino et al, 2011;Gunia et al, 2012;Lohse et al, 2018;Shalvi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation